2011
DOI: 10.1055/s-0031-1281825
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 Sequencing in Iranian Children with Crohn’s Disease

Abstract: Crohn's disease (CD) is a chronic inflammatory disease of the gastrointestinal tract. Although the exact etiology of disease is still unknown, mutations in the CARD15/NOD2 gene have been reported in association with CD in several studies. This study was performed to determine whether the CARD15/NOD2 gene confers susceptibility to Iranian pediatric patients with CD. All 12 coding exons of the CARD15/NOD2 gene were sequenced in 16 enrolled pediatric onset CD patients. Sequencing of the CARD15/NOD2 gene showed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is well agreed that the missed lesions on colonoscopy are variable ranging from 10 to 30%, depending on various factors including center expertise. 16 Ours being a tertiary gastroenterology teaching setup with annual rate of more than 2,000 colonoscopies is one of the possible reasons for a high rate of positive colonoscopy findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is well agreed that the missed lesions on colonoscopy are variable ranging from 10 to 30%, depending on various factors including center expertise. 16 Ours being a tertiary gastroenterology teaching setup with annual rate of more than 2,000 colonoscopies is one of the possible reasons for a high rate of positive colonoscopy findings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 21 ] In another study, pediatric CD patients in Iran were not found to carry these mutations. [ 22 ] A study from Morocco also reported no association of the three NOD2 alleles with local CD patients. [ 23 ] However, in Algerian patients, Gly908Arg (SNP12) mutation was significantly more common in CD patients compared to controls, and Arg702Trp (SNP8) mutation was associated with CD outcome and early onset of disease.…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that the frequency of mutation varies in different ethnic populations. Therefore, association studies on the frequency of mutation in patients with the CD should target each population individually before any clinical implication [19]. This study is to our knowledge the first attempt to target the IBD patients in the Black Sea population of Turkey and has potential to be applied in the clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%